Combined open revascularization and endovascular treatment of complex intracranial aneurysms: case series - Rennert, Robert C.; Nguyen, Vincent N.; Abedi, Aidin; Atai, Nadia A.; Carey, Joseph N.; Tenser, Matthew; Amar, Arun; Mack, William J.; Russin, Jonathan J. (Frontiers in Neurology, 2023)
Background and purpose: The treatment of complex intracranial aneurysms can be challenging with stand-alone open or endovascular techniques, particularly after rupture. A combined open and endovascular strategy can potentially limit the risk of extensive dissections with open-only techniques, and allow for aggressive definitive endovascular treatments with minimized downstream ischemic risk. Materials and methods: Retrospective, single-institution review of consecutive patients undergoing combined open revascularization and endovascular embolization/occlusion for complex intracranial aneurysms from 1/2016 to 6/2022. Results: Ten patients (4 male [40%]; mean age 51.9 ± 8.7 years) underwent combined open revascularization and endovascular treatment of intracranial aneurysms. The majority of aneurysms, 9/10 (90%), were ruptured and 8/10 (80%) were fusiform in morphology. Aneurysms of the posterior circulation represented 8/10 (80%) of the cases (vertebral artery [VA] involving the posterior inferior cerebellar artery [PICA] origin, proximal PICA or anterior inferior cerebellar artery/PICA complex, or proximal posterior cerebral artery). Revascularization strategies included intracranial-to-intracranial (IC-IC; 7/10 [70%]) and extracranial-to-intracranial (EC-IC; 3/10 [30%]) constructs, with 100% postoperative patency. Initial endovascular procedures (consisting of aneurysm/vessel sacrifice in 9/10 patients) were performed early after surgery (0.7 ± 1.5 days). In one patient, secondary endovascular vessel sacrifice was performed after an initial sub-occlusive embolization. Treatment related strokes were diagnosed in 3/10 patients (30%), largely from involved or nearby perforators. All bypasses with follow-up were patent (median 14.0, range 4-72 months). Good outcomes (defined as a Glasgow Outcomes Scale ≥ 4 and modified Rankin Scale ≤ 2) occurred in 6/10 patients (60%). Conclusion: A variety of complex aneurysms not amenable to stand-alone open or endovascular techniques can be successfully treated with combined open and endovascular approaches. Recognition and preservation of perforators is critical to treatment success.